2020
DOI: 10.1111/jgs.16438
|View full text |Cite
|
Sign up to set email alerts
|

Family Identification of Delirium in the Emergency Department in Patients With and Without Dementia: Validity of the Family Confusion Assessment Method (FAM‐CAM)

Abstract: See related editorial by Kennedy et al. in this issueOBJECTIVE: To examine the ability of the family-rated Family Confusion Assessment Method (FAM-CAM) to identify delirium in the emergency department (ED) among patients with and without dementia, as compared to the reference-standard Confusion Assessment Method (CAM). DESIGN: Validation study. SETTING: Urban academic ED. PARTICIPANTS: Dyads of ED patients, aged 70 years and older, and their family caregivers (N = 108 dyads). MEASUREMENTS: A trained reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Our findings underscore the need to distinguish the different roles within the umbrella term of “visitors.” This term disregards or minimizes the critical roles of family and other caregivers of dependent older persons, who serve as surrogate decision‐makers, provide critical medical information, lend emotional support, and advocate for care quality on their behalf. 32 , 33 In the case of persons living with advanced dementia, caregivers serve the invaluable role of interpreting the non‐verbal clues of these persons, who otherwise may communicate pain, fear, overstimulation, or an unmet need only through agitation. 34 The roles of caregivers of older adults may practically parallel those of parents of young children, and the fact that parents were most likely to be granted an explicit exemption from visitor policies in our study demonstrates that hospitals recognize the benefit of such critical roles in the care of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings underscore the need to distinguish the different roles within the umbrella term of “visitors.” This term disregards or minimizes the critical roles of family and other caregivers of dependent older persons, who serve as surrogate decision‐makers, provide critical medical information, lend emotional support, and advocate for care quality on their behalf. 32 , 33 In the case of persons living with advanced dementia, caregivers serve the invaluable role of interpreting the non‐verbal clues of these persons, who otherwise may communicate pain, fear, overstimulation, or an unmet need only through agitation. 34 The roles of caregivers of older adults may practically parallel those of parents of young children, and the fact that parents were most likely to be granted an explicit exemption from visitor policies in our study demonstrates that hospitals recognize the benefit of such critical roles in the care of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This review demonstrates that studies of components of ED care and emergency care needs for PLWDs are wide ranging with little depth on any topic. Studies on components of ED care for PLWDs included a comprehensive geriatric assessment and dedicated ED unit, 26 care partners in the ED and hospital care companions for PLWDs, 22,30 identifying delirium, 4,34,36 fall prevention, 41 admission to a home hospital program, 42 pain assessment and management, 21,28,31,32,43,44 palliative care, 23,37 and changes to the physical environment. 27,33 Four studies showed improvement in patient-centered outcomes or health services use: a comprehensive geriatric assessment and dedicated ED unit, 26 stimulation reduction and noncontact monitoring, 33 dementia companions, 22 and hospital at home program.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies evaluated assessments to detect delirium superimposed on dementia. 24,34,36 The Family Confusion Assessment Method 24,34 demonstrated a sensitivity of 61%, specificity of 74%, and a positive likelihood ratio of 2.2. A positive Family Confusion Assessment Method score was associated with increased hospitalization, ED visit, and mortality.…”
Section: Components Of Ed Carementioning
confidence: 99%
“…In this study, in the emergency department setting, the authors tested the ability of the FAM-CAM to detect delirium in patients with or without dementia compared with the reference standard, the CAM. In addition, the authors had the objective to examine whether the FAM-CAM can perform similarly in patients with or without dementia (Mailhot et al, 2020). 52) 45 ( 90) -…”
Section: Discussionmentioning
confidence: 99%